Estimating intra-seasonal photosynthetic discrimination and water use efficiency using δ13C of leaf sucrose in Scots pine - Tang, Yu; Schiestl-Aalto, Paulina; Lehmann, Marco M; Saurer, Matthias; Sahlstedt, Elina; Kolari, Pasi; Leppä, Kersti; Bäck, Jaana; Rinne-Garmston, Katja T (Oxford University Press (OUP), 2022)
Sucrose has a unique role in recording environmental and physiological signals during photosynthesis in its carbon isotope composition (δ13C) and transport of the signal to tree rings. Yet, instead of sucrose, total organic matter (TOM) or water-soluble carbohydrates (WSC) are typically analysed in studies that follow δ13C signals within trees. To study how the choice of organic material may bias the interpretation of δ13C records, we used mature field-grown Scots pine (Pinus sylvestris) to compare for the first time δ13C of different leaf carbon pools with δ13C of assimilates estimated by a chamber-Picarro system (δ13CA_Picarro), and a photosynthetic discrimination model (δ13CA_model). Compared with sucrose, the other tested carbon pools, such as TOM and WSC, poorly recorded the seasonal trends or absolute values of δ13CA_Picarro and δ13CA_model. Consequently, in comparison with the other carbon pools, sucrose δ13C was superior for reconstructing changes in intrinsic water use efficiency (iWUE), agreeing in both absolute values and intra-seasonal variations with iWUE estimated from gas exchange. Thus, deriving iWUE and environmental signals from δ13C of bulk organic matter can lead to misinterpretation. Our findings underscore the advantage of using sucrose δ13C to understand plant physiological responses in depth.
Keywords: Cavity-ringdown spectrophotometer; photosynthetic carbon isotope discrimination model; Pinus sylvestris L.; starch; total organic matter; water-soluble carbohydrates